(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Steel is one of the most used metals for implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Allergy of steel-implants”. All published articles related to “Allergy of steel-implants” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps. This article had set the objective to consolidate the scientific literature regarding “Allergy of steel-implants” and also to find out the trends related to the same. The most active journals in this research domain were the Contact Dermatitis, Injury, and Journal of Paediatric Surgery. The most active country was the United States of America. The leading organization engaged in the research regarding allergy of steel-implants were University Hospital in Munich and Ludwig- Maximilian University of Germany. The most active authors who had made valuable contributions related to the allergy of steel implants were Summer B. and Thomas P.